GA document 122 :. (Tokyo : A.D.A. edita, 2012)
- Coop Himmelblau: Busan Cinema Center, Busan International Film Festival, Busan, South Korea##- Tod Williams & Billie Tsien: Barnes Foundation — New Philadelphia Campus, Philadelphia, Pennsylvania, U.S.A.##- Renzo Piano: Building Workshop, Ronchamp Gatehouse and Monastery, Ronchamp, Haute Saone, France##- Steven Holl: Glasgow School of Art, Glasgow, U.K.##- Frank O. Gehry: Hong Kong Residential, Hong Kong, China##- Dellugan Meissl Associated Architects: Eye Film Institute, Amsterdam, The Netherlands##- Herzog & de Meuron and Ai Weiwei: Serpentine Gallery Pavilion 2012, London, U.K.##- Morphosis: Morphosis Los Angeles, Los Angeles, California, U.S.A.##- Morphosis: Eni Exploration & Production Management Center, San Donato Milanese, Italy##- Kengo Kuma: Xinjin Zhi Museum, Xinjin, Chengdu, China##-
boek